Hilbert schemes of nonreduced divisors in Calabi–Yau threefolds and W-algebras - Chuang, Wu Yen; Creutzig, Thomas; Diaconescu, Duiliu Emanuel; Soibelman, Yan (European Journal of Mathematics, 2021)
A W-algebra action is constructed via Hecke transformations on the equivariant Borel–Moore homology of the Hilbert scheme of points on a nonreduced plane in three-dimensional affine space. The resulting W-module is then identified to the vacuum module. The construction is based on a generalization of the ADHM construction as well as the W-action on the equivariant Borel–Moore homology of the moduli space of instantons constructed by Schiffmann and Vasserot.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Hilbert schemes; Quiver representations; W-algebras